Dependency of Tharu communities on wild plants: A case study of Shankarpur, Kanchanpur district - Bhattarai, S; Pant, B; Upadhyaya, CP (Banko Janakari, 2013)
Tharu communities are rich in indigenous knowledge of managing environmental resources and coping with environmental stress. The dependency pattern of these communities on wild plants and their role in conservation of wild plants should be identified and explored. This study was carried out with the purpose of assessing dependency pattern of these communities on wild plants and understanding their attitude as well as role in conservation. Both qualitative and quantitative data were collected from concerned stakeholders. Primary data were supplemented and verified from key informants, field observation and secondary sources. Among the four categories of dependency, majority of the respondents were found under category dependent followed by most dependent and somewhat dependent, respectively, but minority of them were found under category not dependent. Almost all of the respondents were found to have played some role in wild plant conservation. Their attitude towards forest and resource conservation was positive, yet they were not satisfied with the traditional mechanism of forest conservation. The traditional approach of managing forest should, therefore, be modified and a new community-oriented approach should be promoted. DOI: http://dx.doi.org/10.3126/banko.v21i1.9062 Banko Janakari, Vol. 21, No. 1 2011; 35-40